Epidermal Immunity and Function: Origin in Neonatal Skin - Visscher, Marty O.; Carr, Andrew N.; Narendran, Vivek (Frontiers in Molecular Biosciences, 2022)
The fascinating story of epidermal immunity begins in-utero where the epidermal barrier derives from ectoderm, evolves through carefully orchestrated biological processes, including periderm formation, keratinocyte differentiation, proliferation, cornification and maturation to generate a functional epidermis. Vernix caseosa derives from epidermal cells that mix with sebaceous lipids and coat the fetus during late gestation, likely to provide conditions for cornification. At birth, infants dramatically transition from aqueous conditions to a dry gaseous environment. The epidermal barrier begins to change within hours, exhibiting decreased hydration and low stratum corneum (SC) cohesion. The SC varied by gestational age (GA), transformed over the next 2-3 months, and differed considerably versus stable adult skin, as indicated by analysis of specific protein biomarkers. Regardless of gestational age, the increased infant SC proteins at 2-3 months after birth were involved in late differentiation, cornification and filaggrin processing compared to adult skin. Additionally, natural moisturizing factor (NMF), the product of filaggrin processing, was higher for infants than adults. This suggests that neonatal skin provides innate immunity and protection from environmental effects and promotes rapid, continued barrier development after birth. Functional genomic analysis showed abundant differences across biological processes for infant skin compared to adult skin. Gene expression for extracellular matrix, development, and fatty acid metabolism was higher for infant skin, while adult skin had increased expression of genes for the maintenance of epidermal homeostasis, antigen processing/presentation of immune function and others. These findings provide descriptive information about infant epidermal immunity and its ability to support the newborn’s survival and growth, despite an environment laden with microbes, high oxygen tension and irritants.